Temporal T807 binding correlates with CSF tau and phospho-tau in normal elderly. (30th August 2016) - Chhatwal, Jasmeer P.; Schultz, Aaron P.; Marshall, Gad A.; Boot, Brendon; Gomez-Isla, Teresa; Dumurgier, Julien; LaPoint, Molly; Scherzer, Clemens; Roe, Allyson D.; Hyman, Bradley T.; Sperling, Reisa A.; Johnson, Keith A.
Abstract : Objective: To better understand cross-sectional relationships between CSF and PET measures of tau pathology, we compared regional and global measures of 18 F-T807 (AV-1451) PET to CSF protein levels of total tau (t-tau), phosphorylated tau (p-tau), and β-amyloid 1–42 (Aβ42). Methods: T-tau, p-tau, and Aβ42 levels were assessed using INNOTEST xMAP immunoassays. Linear regression was used to compare regional and global measures of 18 F-T807 standardized uptake value ratios (SUVR) to CSF protein levels using data from 31 cognitively unimpaired elderly participants in the Harvard Aging Brain study. Results: After controlling for sex and age, total cortical 18 F-T807 binding was significantly correlated with p-tau (partial r = 0.48; p < 0.01) and at trend level with t-tau (partial r = 0.30; p = 0.12). Regional 18 F-T807 measures were more strongly correlated with CSF protein levels than the global measure, with both t-tau and p-tau significantly correlated with 18 F-T807 SUVR in entorhinal, parahippocampal, and inferior temporal cortical regions (partial r = 0.53–0.73). Peak correlations between CSF and PET measures of tau were similar to those between CSF and PET measures of amyloid burden. Finally, we observed significantly higher temporal T807 SUVR in individuals with high amyloid burden. Conclusions: These data support the link between 18 F-T807 PET and CSF measures of tau pathology. In these cognitively normal individuals with 18 F-T807 binding largely restricted to the temporal lobe, 18 F-T807 SUVR in temporal regions appeared more reflective of CSF t-tau and p-tau than a total cortical measure.